Implementasi Loker Digital Berbasis Biometrik Untuk Keamanan Barang Pada Tempat GYM Berbasis Website - Mardhiah Masril; Hasri Awal; Fitra Rahmadona (Jurnal Ilmu Komputer dan Informatika | E-ISSN : 3063-9026, 2026)
The increasing public awareness of the importance of health and fitness has led to a growing number of gym users. This condition requires the availability of safe and efficient supporting facilities, one of which is a secure locker system for storing personal belongings. Conventional locker systems that rely on physical keys have several weaknesses, such as the risk of lost keys, potential misuse, and difficulties in real-time monitoring. This research aims to design and implement a biometric-based digital locker system for securing belongings in gym facilities using a web-based platform. The proposed system utilizes fingerprint authentication as the main access key, supported by a load cell sensor to measure the weight of stored items, a reed switch sensor to detect forced opening attempts, and a buzzer as a warning alarm. All user data and locker activity records are managed through a website developed using PHP and MySQL, integrated with a microcontroller to enable real-time monitoring by gym administrators. The results of this research indicate that the system is able to improve security, enhance locker management efficiency, and provide greater convenience for users through a modern and centralized authentication mechanism. The implementation of this system is expected to minimize the risk of item loss and increase user trust in gym facilities.